2014
DOI: 10.1002/bdra.23332
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal single nucleotide polymorphisms in genes regulating glucose metabolism and risk for neural tube defects in offspring

Abstract: The AA genotype in maternal GCKR rs780094 is associated with an increased risk for NTDs and spina bifida in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…NTDs are recognized to have a complex etiology, mainly involving both genetic and environmental factors. Several observations supported the opinion that genetic factors mainly involve the planar cell polarity (PCP) signaling pathway [13, 14], folate metabolism pathway [15], and glycometabolism pathway [16]. Nuritional factors is the most common environmental factor influencing susceptibility to disease.…”
Section: Discussionmentioning
confidence: 99%
“…NTDs are recognized to have a complex etiology, mainly involving both genetic and environmental factors. Several observations supported the opinion that genetic factors mainly involve the planar cell polarity (PCP) signaling pathway [13, 14], folate metabolism pathway [15], and glycometabolism pathway [16]. Nuritional factors is the most common environmental factor influencing susceptibility to disease.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that maternal mutations of relevant genes involved in folate metabolism are associated with an increased risk for neural tube or congenital heart defects [170][171][172]. Similar findings were demonstrated for maternal polymorphisms involved in glucose metabolism [173]. Such drastic teratogenic consequences highlight the possible impact maternal genetic deficiencies can have, regardless of any transmission to the offspring.…”
Section: Interaction Of Parental Genes Parental Environment and Fetamentioning
confidence: 68%
“…A few studies have supported the opinion that genetic factors mainly involve the planar cell polarity signaling pathway,[ 32 33 ] folate metabolism pathway,[ 34 ] and carbohydrate metabolism pathway. [ 35 ] However, the exact mechanism is yet not understood clearly.…”
Section: Discussionmentioning
confidence: 99%